A climatological assessment of Greenland blocking conditions associated with the track of Hurricane Sandy and historical North Atlantic hurricanes. (22nd April 2014) - Mattingly, Kyle S.; McLeod, Jordan T.; Knox, John A.; Shepherd, J. Marshall; Mote, Thomas L.
ABSTRACT In late October 2012, an extreme area of high pressure centred near Greenland, known as a 'Greenland block', forced Hurricane Sandy to turn westward into the Northeast coast of the United States. In light of this unusual and catastrophic event, the Greenland blocking conditions associated with Sandy and previous North Atlantic hurricane tracks are examined from a climatological perspective. Two primary questions raised by Sandy are investigated: (1) How anomalous were the Greenland blocking conditions observed prior to Sandy's landfall? (2) Were North Atlantic hurricane tracks in the historical record affected by Greenland blocking conditions in a manner similar to Sandy? The measure of blocking strength used to answer these questions is the Greenland Blocking Index (GBI), which is calculated as the spatial average of 500 hPa heights over the Greenland region. The GBI prior to Sandy's landfall was found to be more typical of late June conditions, exceeding the 90th percentile of late October climatology during the entire preceding week and peaking at near‐record values (99.8th percentile) on 25 October. Analysis of the GBI in relation to past North Atlantic hurricane tracks shows that above‐normal GBI values were associated with a southward displacement of hurricane tracks and an increased concentration of tracks near the Northeast US coast. Additionally, composites of atmospheric conditions for 'anomalous' hurricane tracks (defined as tracks with an initial bearing angle between 90° and 360°) revealed an atypical area of high pressure centred over the Canadian Maritimes during these events, whereas near‐climatological conditions of atmospheric pressure over the North Atlantic prevailed for 'normal' hurricane tracks. However, variations in Greenland blocking conditions were not associated with significant changes in the frequency of anomalous North Atlantic hurricane tracks.